2019
DOI: 10.13102/sociobiology.v66i2.3680
|View full text |Cite
|
Sign up to set email alerts
|

Pollen analysis of honey samples produced in the counties of Santa Helena and Terra Roxa, western Region of Paraná, Southern Brazil

Abstract: A melissopalinologia foi utilizada para determinar a origem botânica do mel, importante para sua rastreabilidade. Quarenta amostras de mel dos municípios de Santa Helena (20) e Terra Roxa (20), região oeste do Paraná, foram analisadas de acordo com os tipos de pólen e comparações com os catálogos de pólen e literatura especializada. Em relação à qualidade analítica, foram identificados 300 grãos de pólen por amostra. Nas amostras de Santa Helena, foram encontrados 71 tipos de pólen de 24 famílias, classificado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
3
Order By: Relevance
“…During this period, there are flowering grapes from Japan (Hovenia dulcis), abundant species in the study area, mainly in the lakeside forests of Itaipu bi-national hydroelectric (Camargo et al, 2014). Moraes et al (2019) verified that in honey samples from the lake area, there is a predominance of pollen type H. dulcis in most of the honey sampled, characterized as monofloral of light shades. Nascimento et al (2018) found out that monofloral honey of this species has light shades, as well as a total phenol content of 30.5 mg GAE/100 g -1 and 0.2 mg EQ/100 g -1 of flavonoids.…”
Section: Antioxidant Activitymentioning
confidence: 63%
See 2 more Smart Citations
“…During this period, there are flowering grapes from Japan (Hovenia dulcis), abundant species in the study area, mainly in the lakeside forests of Itaipu bi-national hydroelectric (Camargo et al, 2014). Moraes et al (2019) verified that in honey samples from the lake area, there is a predominance of pollen type H. dulcis in most of the honey sampled, characterized as monofloral of light shades. Nascimento et al (2018) found out that monofloral honey of this species has light shades, as well as a total phenol content of 30.5 mg GAE/100 g -1 and 0.2 mg EQ/100 g -1 of flavonoids.…”
Section: Antioxidant Activitymentioning
confidence: 63%
“…Nascimento et al (2018) found out that monofloral honey of this species has light shades, as well as a total phenol content of 30.5 mg GAE/100 g -1 and 0.2 mg EQ/100 g -1 of flavonoids. Between December and March, the honey got darker, which may be linked to the Eucalyptus flowering, quite prevalent in the region (Sekine et al, 2019;Camargo et al, 2014) and significantly present in the honey samples of the region (Sekine et al, 2019;Moraes et al, 2019). It causes an increase in the bioactive compound contents and antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to the high percentage of samples of light shades of honey produced in the region, where the authors observed 67.16% of the samples presented light amber color (Galhardo et al, 2020). This characteristic of honey from the Western region is associated with a botanical origin that has a dominance of Hovenia dulcis (Moraes et al, 2019) which presents lighter shades of honey (Nascimento et al, 2018).…”
Section: Bioactive Compoundsmentioning
confidence: 93%
“…There are other compounds of honey that contribute in this process, such as its osmolarity, acidity, lysozyme, phenolic phyto-chemical compounds and flavonoids (Olaitan et al, 2007;Brudzynski et al, 2012;Ewnetu et al, 2013;Hegazi et al, 2017;Hussain, 2017;Bucekova et al, 2018). The honey is a natural product, can vary depending on factors such as processing, bee species, botanical origin, a period of the year, rainfall patterns and geographic location (Silva et al, 2016;Moraes et al, 2019;Aydogan-Coskun et al, 2019;Braga et al, 2020;Wabaidur et al, 2020;Yaqub et al, 2020). These factors directly interfere with the composition of pollen and nectar collected by bees (Al-Waili et al, 2011;Bucekova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%